Creatine supplementation and its effect on musculotendinous stiffness and performance - Watsford, M. L.; Murphy, A. J.; Spinks, W. L.; Walshe, A. D. (The Journal of Strength and Conditioning Research, 2003)
Anecdotal reports suggesting that creatine (Cr) supplementation may cause side effects, such as an increased incidence of muscle strains or tears, require scientific examination. In this study, it was hypothesized that the rapid fluid retention and"dry matter growth" evident after Cr supplementation may cause an increase in musculotendinous stiffness. Intuitively, an increase in musculotendinous stiffness would increase the chance of injury during exercise. Twenty men were randomly allocated to a control or an experimental group and were examined for musculotendinous stiffness of the triceps surae and for numerous performance indices before and after Cr ingestion. The Cr group achieved a significant increase in body mass (79.7 ± 10.8 kg vs. 80.9 ± 10.7 kg), counter movement jump height (40.2 ± 4.8 cm vs. 42.7 ± 5.9 cm), and 20-cm drop jump height (32.3 ± 3.3 cm vs. 35.1 ± 4.8 cm) after supplementation. No increase was found for musculotendinous stiffness at any assessment load. There were no significant changes in any variables within the control group. These findings have both performance- and injury-related implications. Primarily, anecdotal evidence suggesting that Cr supplementation causes muscular strain injuries is not supported by this study. In addition, the increase in jump performance is indicative of performance enhancement in activities requiring maximal power output.